Evaluation of the Properties of Magnetite (Fe3O4) Nanoparticles Prepared by the Green Method Using Phoenix dactylifera Extract - Shanan, Zainab J.; Ali, Huda M.J.; Abdalameer, Nisreen Kh. (Iraqi Journal of Science, 2024)
Iron oxide (Fe3O4) nanoparticles were synthesized via an eco-friendly green approach by adding Phoenix dactylifera extract to the aqueous solution of ferric chloride. The effect of annealing temperature (Ta) (100-150) °C on particle size was studied. X-ray diffraction (XRD), UV-visible spectroscopy, atomic force microscopy (AFM), and field emission scanning electron microscopy (FESEM) were used to evaluate the produced nanoparticles. According to XRD spectra, the crystallite size of the samples was determined using the Scherrer formula. AFM and FE-SEM were used to determine surface morphology. A UV-Vis optical spectroscopic examination was carried out to determine the band gap energy of the iron oxide nanoparticles. It was found that with the increased temperature from 100 to 150 oC, the band gap energy of the produced Fe3O4 NPs decreased. The size of the produced particles increased with increasing temperature, as evidenced by AFM and XRD spectra.